St3gal5-mediated sialylation of glyco-CD177 on neutrophils restricts neuroinflammation following CNS injury - Tingting Huang; Wanqing Xie; Yunlu Guo; Yan Li; Jiemin Yin; Xia Jin; Yezhi Ma; Yueman Zhang; Dan Huang; Caiyang Chen; Xin Wang; Ziyu Zhu; et al. (Proceedings of the National Academy of Sciences, 2025)
Neutrophils are the most abundant circulating leukocyte population that play critical roles in neuroinflammation following central nervous system (CNS) injury. CD177, a glycoprotein on neutrophils, is emerging as an important immune regulator which can fundamentally affect multiple human inflammatory diseases. However, the role and regulatory mechanism of CD177 glycobiology of neutrophils in neuroinflammation remain elusive. Here, we show that CD177 + neutrophils expand significantly and infiltrate the injured brain following CNS injury both in the human and mouse. Using single-cell RNA sequencing and genetic approaches, we find CD177 + neutrophils as an anti-inflammatory subset that is critical for modulating neuroinflammation after CNS injury. We further identify St3gal5, a sialyltransferase (ST), that can mediate the sialylation and cell surface presentation of glyco-CD177 on neutrophils. Glycoproteomics reveal downregulated sialylation levels in St3gal5-deficient neutrophils. Neutrophil-specific depletion of St3gal5 prevents the cell surface presentation of CD177 on brain-infiltrated neutrophils and exacerbates neuroinflammation. Administration of the FDA-approved anticonvulsant valproic acid (VPA), an St3gal5 upregulator, promotes the glycosylation of neutrophils and attenuates neuroinflammation following CNS injury. Our study reveals a glycoimmuno-regulatory effect of neutrophils and suggests VPA as a neutrophil glycobiology targeting approach to combat neuroinflammation following CNS injury.